Shaping ability of modern Nickel-Titanium rotary systems on the preparation of printed mandibular molars - İRİBOZ, EMRE (My University, 2022)
© 2022 Wolters Kluwer Medknow Publications. All rights reserved.Introduction: This study aimed to evaluate the shaping ability of TruNatomy (Dentsply Maillefer, Ballaigues, Switzerland), VDW.ROTATE (VDW GmbH, Munich, Germany) and ProTaper Gold (Dentsply Maillefer, Ballaigues, Switzerland) during the preparation of resin-printed mandibular molar mesial root canals. Materials and Methods: Thirty-three printed resin-based mandibular mesial roots with two canals were obtained from extract tooth cone-beam computed tomography (CBCT) image. The printed teeth were divided into three groups (n = 11) according to the system used for root canal preparation: TruNatomy, VDW.ROTATE, and ProTaper Gold. The specimens were scanned using CBCT imaging before and after root canal preparation. Then images were registered using a dedicated software and changes in the canal area, volume, untouched canal surface, and the maximum and minimum dentin wall wear were calculated. Statistical Analysis Used: Data were statistically analyzed using Shapiro-Wilk for normality, one-way ANOVA, and Tukey or Kruskal-Wallis H tests with alpha set at 5%. Results: No differences were observed for changes in the canal area, volume, untouched canal surface area, and minimum dentine wall wear parameters for the whole canal length (P > 0.05). The mean of untouched canal surface area for the TruNatomy, VDW.ROTATE, and ProTaper Gold was 40%, 44%, and 44%, respectively. The maximum dentine wall wear was significantly lower in the ProTaper Gold group than in the TruNatomy and VDW.ROTATE groups (P < 0.05). Conclusions: TruNatomy, VDW.ROTATE, and ProTaper Gold systems showed similar shaping ability in printed resin-based mandibular mesial roots without clinically significant errors. A large amount of untouched canal surface area was observed for all systems.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; General Dentistry; Printed resin teeth; ProTaper Gold; three-dimensional printing; TruNatomy; VDW.ROTATE